The Large-Mass Phenotype of Uterine Smooth Muscle Tumor of Uncertain Malignant Potential (STUMP): A Clinicopathological Analysis of 37 Cases in Indonesia Using WHO 2021 and Modified Stanford Criteria - Yuliza Ariani; Henny Mulyani; Noza Hilbertina; Yenita; Aswiyanti Asri; Tofrizal; Loli Devianti; Hera Novianti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Uterine smooth muscle tumor of uncertain malignant potential (STUMP) presents a diagnostic dilemma, especially in Southeast Asian populations, where delayed presentation often leads to advanced tumor burden. This study aimed to characterize the clinicopathological profile of STUMP in Indonesia using the 2021 WHO Classification and modified Stanford parameters. Methods: A descriptive study analyzed 37 STUMP cases diagnosed between 2023 and 2025 at a tertiary referral center in West Sumatra. A panel of pathologists re-evaluated archival slides for atypia, mitotic activity, necrosis, and growth patterns, establishing inter-observer reliability. Fisher’s Exact Test was employed to correlate tumor size with morphological markers of aggression. Results: The cohort demonstrated a distinct large-mass phenotype, with 54.1% of tumors exceeding 10 cm and a median diameter of 14.5 cm. Pathological review classified 56.8% of cases into WHO Group 4 (atypia with ambiguous mitosis). A statistically significant correlation was identified between tumor size >10 cm and the presence of infiltrative growth margins (81.1%; p=0.034). Conclusion: Indonesian STUMP cases are distinctively characterized by massive size and high rates of infiltrative growth, likely driven by prolonged natural history. The prevalence of ambiguous mitotic figures underscores the utility of the WHO Group 4 category in resource-limited settings. These findings advocate for aggressive surgical management and wider resection margins in large-mass variants to mitigate local recurrence risk.